Is neutrophil/lymphocyte and platelet/lymphocyte ratio a predictive factor for the fibrous stage in patients with chronic hepatitis B? (Annals of Medical Research, 2021)
Aim: Neutrophil-lymphocyte ratio (NLR) and platelet-lymphocyte ratio (PLR) are an inexpensive inflammatory marker that can beeasily obtained from the blood count and can be used in many chronic diseases. In our study, we aimed to investigate the relationshipbetween fibrosis stage and NLR, PLR in patients with chronic hepatitis B virus (HBV).Materials and Methods: 173 patients with chronic HBV were included in the study. The demographic data and hemogram parameters of all patients were recorded. Histopathological data of the patients were documented. Accompanying comorbid diseases, medicationsand previous operations were questioned. In chronic HBV patients, fibrosis level was compared with hematological parameters.Results: A total of 173 patients, 100 (57.8%) of whom were male, were included in the study. As a result of the liver biopsy; mildfibrosis (steage/1-2) in 83(47.9%) patients, moderate fibrosis (steage/3-4) in 35(20.3%) patients and advanced fibrosis (stage/5-6)in 55(31.8%) patients. In advanced fibrosis group, liver function tests and bilirubin levels were significantly higher and albumin levelwas significantly lower (p